Circular economy strategies and practices: A case study with multiple participants in the packaging sector in Brazil - Streit, Jorge Alfredo Cerqueira (2023)
This research analyses the leading strategies and practices for transforming Brazil's Circular Economy of packaging. In-depth semi-structured interviews (n=53) were conducted with stakeholders active in the Brazilian packaging sector and triangulated with document analysis. The main strategies identified were environmental education programs, MSW diversion practices, environmental crimes (regeneration) inspection, efficient use of products, and waste reduction (optimisation). As for sharing, the inequality resulting from regional differences in logistics infrastructure was highlighted. The paper has theoretical contributions, such as applying the ReSOLVE method and practices for generating social, environmental and economic benefits.